Implementasi Strategi Pembelajaran PQ4R (Preview, Question, Read, Reflect, Recite, Review) dalam Meningkatkan Hasil Belajar Peserta Didik pada Mata Pelajaran Akidah Akhlak Kelas X - Supratiwi Supratiwi (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
This research aims to investigate the implementation of the PQ4R learning strategy in enhancing students’ learning putcomes in the subject of Akidah Akhlak for grade X at MAS Al Falah Limboto Barat. The method employed in this study is Classroom Action Research (CAR) with Kemmis and Taggert CAR model specifications, consisting of 2 cycles each comprising planngin, action, observing and reflection. The research subject are students from class X MIA I which totaling 19 individuals. Data were obtained from students’ learning outcomes, mid-term exam results, questionnaires, interviews with teachers and students, as well as field notes. The results of this research indicate an improvement in students’ learning outcomes, starting from cycle 1, meeting 1 reaching 58% to meeting 2 which reached 63%. In cycle II, a consistent improvement was obtained in meeting 1 and 2, totaling 95%. Data analysis was conducted using quantitative and qualitative descriptive analysis. Additionally, through the implementation of the PQ4R strategy. Students’ active involvement in providing responses during each teacher’s introduction, participation in discussions, sincerity in reading and answering questions, and expressing opinions significantly increased. Therefore, it can be concluded that the PQ4R strategy can enhance students’ learning putcomes and is activating students’ roles, so, making it suitable for application in the learning process.